Microwave single-tone optomechanics in the classical regime. (7th May 2021) - Golokolenov, Ilya; Cattiaux, Dylan; Kumar, Sumit; Sillanpää, Mika; Mercier de Lépinay, Laure; Fefferman, Andrew; Collin, Eddy
Abstract: We report on the quantitative experimental illustration of elementary optomechanics within the classical regime. All measurements are performed in a commercial dilution refrigerator on a mesoscopic drumhead aluminium resonator strongly coupled to a microwave cavity, using only strict single-tone schemes. Sideband asymmetry is reported using in-cavity microwave pumping, along with noise squashing and back-action effects. Results presented in this paper are analysed within the simple classical electric circuit theory, emphasizing the analogous nature of classical features with respect to their usual quantum description. The agreement with theory is obtained with no fitting parameters. Besides, based on those results a simple method is proposed for the accurate measurement of the ratio between microwave internal losses and external coupling.